Thermal conditions of the battery cell of an electrochemical energy storage system under intense electrochemical and chemical reactions; Journal of the Brazilian Society of Mechanical Sciences and Engineering; Vol. 47 - Kuznetsov G. V. Geny Vladimirovich (2025, 2025)
Title screen